High school students' perceptions of the benefits of the group work to their English language learning: a survey research in Ngoc Tao High School - Vũ, Thị Hải (ĐHNN, 2017)
Learners' belief about language learning. The role of group work in language learning. Limitations of group work. Studies on the use of group work. Students; attitudes towards group work. Students' opinions of the main benefits and limitations of group work according to grades.